2023
DOI: 10.1364/ol.486014
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional color shift suppression of full-color micro-LED displays with enhanced light extraction efficiency

Abstract: The three-primary-color chip array is the most straightforward to realize full-color micro-LED displays. However, the luminous intensity distribution shows high inconsistency between the AlInP-based red micro-LED and GaN-based blue / green micro-LEDs, resulting in the issue of angular color shift with different viewing angles. This Letter analyzes the angular dependence of color difference of conventional three-primary-color micro-LEDs, and proves that the inclined sidewall with homogeneous Ag coating has a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The glass substrate with refractive index of 1.51 and thickness of 1 mm was used as the waveguide, and the transverse period of 422.8 nm was used to prepare the waveguide structure of this configuration with the coupling grating size of 45 mm × 25 mm. LCOS optical engine (LCE2201F), LCOS optical engine provides 30.6 °× 17.7 °to input virtual images [19] . A camera was placed 15 mm away from the coupling area to capture the imaging results of the AR.…”
Section: Methodsmentioning
confidence: 99%
“…The glass substrate with refractive index of 1.51 and thickness of 1 mm was used as the waveguide, and the transverse period of 422.8 nm was used to prepare the waveguide structure of this configuration with the coupling grating size of 45 mm × 25 mm. LCOS optical engine (LCE2201F), LCOS optical engine provides 30.6 °× 17.7 °to input virtual images [19] . A camera was placed 15 mm away from the coupling area to capture the imaging results of the AR.…”
Section: Methodsmentioning
confidence: 99%
“…An inclined sidewall has often been adopted to redirect the in-plane transverse magnetic (TM) photons toward the substrate for extraction, thus enhancing the LEE of lLEDs. [99][100][101][102][103] For example, it has been shown that deep ultraviolet (DUV) lLEDs (k ¼ 280 nm; chip size ¼ 20 lm) with a sidewall angle of 33 yielded a 19% higher EQE than those with an inclination angle of 75 . 99 This improvement was attributed to the fact that more photons underwent total internal reflection (TIR) with the 33 -inclined sidewall, resulting in a higher LEE [Figs.…”
Section: Efficienct Light Extraction From Lledsmentioning
confidence: 99%
“…Nitride light-emitting diodes (LEDs) have garnered increasing attention and extensive amounts of research due to their low power consumption and compact size [1][2][3]. One common problem facing GaN-based LEDs is that the electrons can be easily injected from the active regions into the p-GaN region, which decreases the recombination of the carriers within the active regions, owing to the high mobility and small effective mass of the electrons.…”
Section: Introductionmentioning
confidence: 99%